TO EVALUATE THE OUTCOME OF SUBLAY OPEN MESH REPAIR IN INCISIONAL HERNIA - Abdul Ghani1 , Muharram Ali Abbasi2 , Ehsanullah Malik3 , Nadia Bhatti4 , Sania Bhatti5 , Waqare-Sahar Shah6 . (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: Incisional hernia is a protrusion of the tissue developed at the site of healing /8scar. This hernia accounts for 15-20% of all abdominal hernias. The causes include respiratory, urological and abdominal problems like chronic cough, difficulty in passing urine and constipation etc. Pregnancy and ascites are also etiological factors. Postoperative wound infections and wound dehiscence are also responsible for developing incisional hernias. Open sublay mesh repair is the best procedure in this regard. OBJECTIVE: - To assess the efficacy of Sublay Mesh repair in patients suffering from incisional hernia. MATERIAL AND METHODS: This is study of one year done in Chandka Medical College Hospital Larkana from March 2019 to February 2020. All the patients were taken from OPD. Clinical History particularly Past history of Surgry was taken. Patients were optimized and fitness was taken for surgery. Mesh of required size was arranged and patients were operated for Open Sublay Mesh repair. Follow up was gotten. RESULTS: Total patients included in this study were 45. Of them, 25(55.5%) were female and 20 (44.4%) were male. Seroma formation was in 9(20%) patients but the placement of Redivac drain resolved the issue instantly. Infection was seen in 1(2.2%) patient only. Recurrence was noted in 1 (2.2%). Flap necrosis was seen in no any patient. The rate of fecal fistula was 0%. CONCLUSION: - Sublay open Mesh repair was the best method in our study with good results and least complication rate.